PEMBELAJARAN MATEMATIKA MELALUI PEMECAHAN MASALAH: URGENSI DAN PENERAPANNYA - Arnoldus Helmon; Eliterius Sennen (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
Problem solving competency is an urgent competency in 21st century indicated by human resource competing. Therefore, learning in schools, included mathematical learning, should addres this challenge. Mathematical learning should be aimed at making students learning about and through problem solving. For this sake, teachers should take atention to multiple factors that impact the effective teaching of problem solving.